A novel rice dull gene, LowAC1, encodes an RNA recognition motif protein affecting Waxyb pre-mRNA splicing - Igarashi, Hidenari (Plant physiology and biochemistry : PPB, 2021)
Copyright © 2021 Elsevier Masson SAS. All rights reserved.